A new hybrid method to estimate the single-diode model parameters of solar photovoltaic panel - Souad Lidaighbi; Mustapha Elyaqouti; Dris Ben Hmamou; Driss Saadaoui; Khalid Assalaou; Elhanafi Arjdal (Energy Conversion and Management: X, 2022)
Today, photovoltaic (PV) panels represent a large part of total power generation. Photovoltaic cells and modules parameter estimation is a relevant field of research that plays a critical role in PV system modeling and simulation. This paper presents a new simple and accurate hybrid method to estimate the five parameters of the single-diode model. The proposed method aims to build a set of equations as functions of the five unknown parameters based on the three remarkable points and the PV datasheet's information. These equations will be used to derive a closed form expression for I0, Iph, Rsh, and Rs. This paper also presents a new simple iterative approach to better estimate the fifth parameter, the ideality factor (n), using only datasheet information. The novelty of this study is to use a new effective simple hybrid method that combines the analytical and the iterative approaches based on the increment of the ideality factor by step of 0.01Vt to achieve the minimum Root Mean Square Error possible. The results reveal that the proposed method outperforms a large number of analytical, numerical, and even the most powerful meta-heuristic algorithms in terms of accuracy, simplicity and reliability.